RANCANG BANGUN APLIKASI SISTEM PANTAU GULA DARAH DIABETES - Indriani (Journal of Information Technology, 2023)
Technology has a very important role in various fields, one of which is in the medical field. the use of technology in the medical field can be used to assist in the management of patient administration data up to medical examinations of patients related to medical data. Cases of diseases that require management of medical data on a routine scale, namely Diabetes Mellitus (DM). According to the International Diabetes Federation (IDF) Data Atlas for 2021, Indonesia is ranked 5th with the largest number of diabetics in the world by showing an increase in the number of sufferers almost doubling in the past two years, namely 19.46 million cases [1]. With this large number of cases, the management of Diabetes Mellitus (DM) is needed in patients regularly. Because the fundamental thing in the management of DM, especially type 2 DM is a change in lifestyle, including a good diet and regular exercise. The individual's ability to manage daily life, control, and reduce the impact of the disease suffered by patients is known as self-management. The main objective of the DM monitoring system in the management of DM is to regulate glucose levels within normal limits to reduce symptoms and prevent complications that occur in people with DM. The research method used in the development of this self-management application is the Scrum method. The research results obtained are an information system to monitor diabetes blood sugar that makes it easier for diabetics to monitor their health independently.